Utility of Red Blood Cell Parameters and Indices of Iron Homeostasis in Evaluation of Microcytosis without Anemia or with Mild Anemia: A Diagnostic Accuracy Study - Thambiraj, Paruvathavarthini; Nanda, Nivedita; Kar, Rakhee (Journal of Laboratory Physicians, 2023)
Introduction Asymptomatic microcytosis may be a prelude to microcytic hypochromic anemia of varied causes. Evaluation of red cell indices may help delineate cases needing further investigation like hemoglobin high-performance liquid chromatography (Hb-HPLC). In addition, markers of iron homeostasis will help confirm iron-deficient erythropoiesis (IDE)/iron deficiency anemia (IDA).Materials and Methods This was a single institutional hospital-based study over a period of 18 months. The sample size was 60, which include all age groups, males and females, and values of mean corpuscular volume (MCV) < 80 fL, Hb ≥ 10g/dL were taken as the inclusion criteria. Various derived red cell indices, Hb-HPLC, and iron parameters were assessed. Hb-HPLC and serum ferritin with transferrin saturation (TSAT) values were taken as the gold standard for diagnosis of hemoglobinopathies/thalassemia trait and IDA/IDE, respectively.Results Out of 60 samples, 24 (40%) and 36 (60%) had abnormal and normal proportion of Hb variants, respectively. In total, seven indices were evaluated, which included Mentzer's index, red cell distribution width index, Ehsani's index, Sirdah's formula, Matos–Carvalho index, Shine and Lal index, and Sehgal's index. The Shine and Lal index showed better sensitivity (89%) and specificity (73%) for diagnosing pure thalassemia trait. The Sirdah index showed better sensitivity (78%) and specificity (42%) in diagnosing IDE/IDA. Ferritin showed better sensitivity (74%) and specificity (84%) in diagnosing pure IDA and TSAT showed better results in diagnosing IDA/IDE.Conclusion The Shine and Lal index and Mentzer index can be used as screening tools and help detect subjects who require appropriate follow-up with confirmation by Hb-HPLC. Serum ferritin remains the gold standard for diagnosis of IDA.
Keywords: derived red cell indices; diagnostic accuracy; iron parameters; IDA/IDE; Hb-HPLC; screening tool; Mentzer index